2008
DOI: 10.1007/s10295-008-0429-3
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid producing potential of lactobacilli isolated from the rumen of cattle

Abstract: Lactobacilli isolated from the rumen of cattle were subjected to morphological and biochemical characterizations followed by PCR-based identification. Among isolates, Lactobacillus brevis was found to be the most prevalent species in the rumen. For in vitro conjugated linoleic acid (CLA) production, the two isolates of L. brevis and one each of Lactobacillus viridescens and Lactobacillus lactis were selected. The sunflower oil (i.e., 0.25, 0.5 and 1.0%; a rich source of linoleic acid) was added to skim milk as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…In all 19 lactobacilli c9, t11 isomer were reported as the most predominant isomer in LA-MRS and LA-SM mediums. These findings are in complete agreement with previous findings of isomer variability (SosaCastañeda et al 2015;Andrade et al 2012;Puniya et al 2008).…”
Section: Cla Isomers Analysis By Gcsupporting
confidence: 93%
See 1 more Smart Citation
“…In all 19 lactobacilli c9, t11 isomer were reported as the most predominant isomer in LA-MRS and LA-SM mediums. These findings are in complete agreement with previous findings of isomer variability (SosaCastañeda et al 2015;Andrade et al 2012;Puniya et al 2008).…”
Section: Cla Isomers Analysis By Gcsupporting
confidence: 93%
“…Of these, 44% correspond to L. plantarum, L. gasseri (30%), L. fermentum (21%) and L. salivarius (5%). Earlier, several different CLA producing species of lactobacilli (L. plantarum, L. acidophilus, L. casei and L. fermentum) obtained from different sources were reported by several authors (Andrade et al 2012;Puniya et al 2008;Ando et al 2003;Lee et al 2007). Our results, in respect to CLA production by L. plantarum and L. fermentum are in complete with earlier findings; however, the current study indicated a major proportion of L. gasseri and few L. salivarius strains also as CLA producers.…”
Section: Lactobacilli Species Characterizationmentioning
confidence: 99%
“…However, when hydrolysed soya oil was added (total fat content 1%) CLA production was 0.63-2.21 mg CLA/g fat. Puniya, Chaitanya, Tyagi, De, and Singh (2008) found that L. brevis isolated from rumen fluid produced 10 mg CLA/g fat in skim milk using sunflower oil (0.25%) as a source of LA, while L. lactis with 1% sunflower oil was 9.22 mg CLA/g fat. The former research work supports the results presented in this study where concentrations of 2.72-3.44 mg CLA/g fat was obtained in skim milk after 24 h using LA as substrate while lower concentrations (0.31-1.53 mg CLA/g fat) were produced when safflower was added.…”
Section: Discussionmentioning
confidence: 98%
“…Genus-specific primer with a universal primer, has been tested for its specificity with 23 strains of lactobacilli (Senan, et al, 2008;Kaushik et al, 2009 andPuniya et al, 2008). The studies concluded that all the 39 isolates furnished an amplified product of 250 bp and were characterized as lactobacilli.…”
Section: Molecular Identificationmentioning
confidence: 99%